Evaluation of Cytotoxicity Effect of Hyptis pectinata Poit (Lamiaceae) extracts using BSLT and MTT methods - Suzery, Meiny; Cahyono, Bambang (JURNAL SAINS DAN MATEMATIKA, 2014)
Hyptis pectinata (Lamiaceae) is a traditional medicinal plants to treat conditions associated with malignant disease. In Indonesia, this plant has not been utilized yet, just as a wild plant. This study aimed to evaluate the anticancer activity of Hyptis pectinata poit extracts which are more beneficial. Methanol extract and various fractions solvents (hexane, dichloromethane, ethyl acetate) were examined their toxicities to shrimp larvae Artemia salina Leach using BSLT method and their anticancer activity in vitro on cells MCF-7 breast cancer using MTT assay method. The toxicity test on shrimp larvae Artemia salina Leach, methanol extracts have LC50: 185.63 Âµg/mL and fractions of hexane, dichloromethane and ethylacetate were obtained at 128.45; 113.32 and 92.54 Âµg/mL successively. Whereas the cytotoxicity test on breast cancer cells MCF-7 resulted that methanol extract Hyptis pectinata poit obtained at IC50: 18.90 Î¼g/mL. Hyptis pectinata poit extract showed good cytotoxic and anticancer activity hence it has a chance to be developed to as anticancer drugs.